’Spot the Difference’: Technical Research into Two Versions of The Lamentation of Christ, attributed to Colijn de Coter - Woltman, Nienke (The Rijksmuseum Bulletin, 2019)
The small, unsigned panel The Lamentation of Christ in the Rijksmuseum’s collection is attributed to Colijn de Coter and dated around 1510-15. There is another, almost identical version in a private collection. Visual analysis and analytical techniques including UV fluorescence, infrared reflectography, X-ray fluorescence (XRF), X-radiography, dendrochronology and paint sample analysis, were used to examine and compare the materials and techniques in both paintings in order to investigate the relationship between the two. Because only a small oeuvre is attributed to De Coter and there has as yet been very little scientific analysis of his paintings, this comparative investigation provides more information about the artist’s workshop practices. This research has revealed that the materials and techniques used in the two versions differ hardly at all and, moreover, correspond to standard practice in early sixteenth-century painting in the Low Countries. The thicker outlines in the underdrawings in both cases indicate that the compositions were traced or copied from the same model. The underdrawings of the two Lamentations also correspond to those in other paintings attributed to the artist. This makes it likely that both versions came from De Coter’s workshop.